Coating composition, film, article, and bearing

The coating composition, featuring a fluorine resin and polyamideimide/epoxy resins, addresses the issue of electrocorrosion and wear in electric vehicle bearings by forming a durable, insulating, and low-friction coating film.

JP2025063868AActive Publication Date: 2025-04-16DAIKIN INDUSTRIES LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2024174856
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-04
Filing Date
2024-10-04
Publication Date
2025-04-16
Estimated Expiration
2044-10-04

AI Technical Summary

Technical Problem

Bearings used in electric vehicles are prone to electrocorrosion due to the flow of electricity, which can lead to surface melting and loss of smoothness, and existing coatings lack sufficient insulation and wear resistance to prevent these issues.

Method used

A coating composition comprising a fluorine resin containing high molecular weight polytetrafluoroethylene and copolymers of tetrafluoroethylene, hexafluoropropylene, and perfluoroalkyl vinyl ether, combined with a polyamideimide resin and/or an epoxy resin, and an organic solvent, which forms a coating film with excellent anti-electrode properties, low friction, and wear resistance.

Benefits of technology

The coating composition effectively prevents electrocorrosion and wear in bearings by providing a robust, insulating, and low-friction coating film that maintains its abrasion resistance and adhesion to the substrate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025063868000001
    Figure 2025063868000001
  • Figure 2025063868000002
    Figure 2025063868000002
  • Figure 2025063868000003
    Figure 2025063868000003
Patent Text Reader

Abstract

To provide a coating composition capable of forming a coating film excellent in electrolytic corrosion prevention and low friction.SOLUTION: This coating composition contains a fluororesin (A) partially or exclusively containing a high molecular weight polytetrafluoroethylene (A-1), a polyamideimide resin and / or an epoxy resin (B), and an organic solvent (C).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to coating compositions, coatings, articles and bearings. [Background technology]

[0002] Patent Documents 1 to 4 describe painting of bearings. In recent years, electric vehicles have become widespread. The bearings described in these documents do not consider problems that may occur when the bearings are used in such electric vehicles. Patent Document 5 discloses a coating material capable of maintaining the wear resistance and sliding properties of a piston in a compressor of an automobile air conditioner. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2000-15720 A [Patent Document 2] Special Publication No. 2022-42162 [Patent Document 3] JP 2008-280485 A [Patent Document 4] JP 2013-85441 A [Patent Document 5] JP 2005-198372 A [Patent Document 6] Patent Publication No. 2022-15680 Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present disclosure is to provide a coating composition capable of forming a coating film that is galvanic corrosion-resistant and has low friction properties and therefore excellent abrasion resistance. [Means for solving the problem]

[0005] The present disclosure relates to A fluororesin (A) containing, in whole or in part, high molecular weight polytetrafluoroethylene (A-1); The coating composition is characterized by containing a polyamideimide resin and / or an epoxy resin (B) and an organic solvent (C).

[0006] The fluororesin (A) preferably further contains one or more copolymers (A-2) made of tetrafluoroethylene, and hexafluoropropylene and / or perfluoroalkyl vinyl ether.

[0007] The copolymer (A-2) preferably has a melt flow rate of 1 to 30 (g / 10 minutes). In the coating composition, the mass ratio of the high molecular weight polytetrafluoroethylene (A-1) to the copolymer (A-2) is preferably (A-1) / (A-2)=10 / 90 to 90 / 10. In the coating composition, the mass ratio of the fluororesin (A) to the polyamideimide resin is preferably fluororesin (A) / polyamideimide resin=40 / 60 to 70 / 30. The polyamide-imide resin preferably has a number average molecular weight of 10,000 to 40,000.

[0008] In the coating composition, the mass ratio of the fluororesin (A) to the epoxy resin is preferably fluororesin (A) / epoxy resin=30 / 70 to 70 / 30. In the coating composition, the epoxy resin preferably has a number average molecular weight of 200-2,500.

[0009] In the coating composition, the polyamideimide resin and / or epoxy resin (B) is a polyamideimide resin, the fluororesin (A) further contains one or more copolymers (A-2) consisting of tetrafluoroethylene and hexafluoropropylene and / or perfluoroalkyl vinyl ether, the copolymer (A-2) having a melt flow rate of 1 to 30 (g / 10 min), the mass ratio of the high molecular weight polytetrafluoroethylene (A-1) to the copolymer (A-2) being (A-1) / (A-2)=5 / 95 to 55 / 45, the mass ratio of the fluororesin (A) to the polyamideimide resin being fluororesin (A) / polyamideimide resin being 40 / 60 to 70 / 30, and the number average molecular weight of the polyamideimide resin being 10,000 to 40,000.

[0010] In the coating composition, it is preferable that the polyamideimide resin and / or epoxy resin (B) is an epoxy resin, the fluororesin (A) further contains one or more copolymers (A-2) consisting of tetrafluoroethylene and hexafluoropropylene and / or perfluoroalkyl vinyl ether, the copolymer (A-2) having a melt flow rate of 1 to 30 (g / 10 min), the mass ratio of the high molecular weight polytetrafluoroethylene (A-1) to the copolymer (A-2) being (A-1) / (A-2)=5 / 95 to 55 / 45, the mass ratio of the fluororesin (A) to the epoxy resin being fluororesin (A) / epoxy resin=30 / 70 to 70 / 30, and the number average molecular weight of the epoxy resin being 200 to 2000.

[0011] The present disclosure also relates to a coating formed from the above-described coating composition. The present disclosure is also directed to an article having the coating. The present disclosure is also a bearing having the above coating. The present disclosure also relates to an article having the above bearing. Effect of the Invention

[0012] The coating composition of the present disclosure has anti-electrolytic corrosion properties and has low friction properties, making it possible to form a coating film that has excellent abrasion resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present disclosure will be described in detail below. Bearings are widely used in the automotive field. Meanwhile, electric vehicles have been expanding into the market in recent years, and bearings are also widely used in electric vehicles.

[0014] Electricity may flow through bearings used in electric vehicles. When electricity flows through a bearing, a phenomenon called galvanic corrosion occurs. This is a phenomenon in which the metal surface of the bearing melts due to sparks caused by the passage of electric current, resulting in loss of surface smoothness. Note that the galvanic corrosion in this disclosure is a completely different phenomenon from the phenomenon in which corrosion of one metal is accelerated when different types of metals come into contact and conduct electricity in a corrosive environment (galvanic corrosion).

[0015] To prevent such electrolytic corrosion, it is preferable to improve the insulation of the bearing. For this reason, it is possible to form an insulating coating film using paint. To prevent electrolytic corrosion, it is necessary to form a film with excellent insulation and wear resistance. If the wear resistance is low, the base material is easily exposed due to wear of the coating film, which causes electricity to flow to the bearing and electrolytic corrosion occurs. In addition, wear powder is generated due to wear of the coating film, and the wear powder itself can become foreign matter and become a factor that inhibits the rotation of the bearing. To obtain wear resistance, low friction is required.

[0016] The coating composition of the present disclosure exhibits particularly excellent performance in coating such bearings.

[0017] (Fluororesin (A)) The coating composition of the present disclosure contains a fluororesin (A). A fluororesin is a resin that partially contains fluorine atoms. Since the fluororesin is a resin that is excellent in low friction, it is particularly suitable for the purpose of the present disclosure. The fluororesin (A) used in the coating composition of the present disclosure contains at least a high molecular weight polytetrafluoroethylene (A-1). By using such a fluororesin, a particularly favorable effect can be obtained in that a coating film that has both insulating properties and abrasion resistance can be formed.

[0018] (High molecular weight polytetrafluoroethylene (A-1)) In the resin composition of the present disclosure, a part or the whole of the fluororesin (A) is high molecular weight polytetrafluoroethylene (hereinafter, this may be referred to as high molecular weight PTFE) (A-1). High molecular weight PTFE means PTFE that is non-melt processable and fibrillating.

[0019] The above-mentioned non-melt processability means that the melt flow rate cannot be measured at a temperature higher than the crystallization melting point according to ASTM D-1238 and D-2116.

[0020] The presence or absence of fibrillation properties can be judged by "paste extrusion," a typical method for molding "high molecular weight PTFE powder," a powder made from a TFE polymer. Paste extrusion is usually possible because high molecular weight PTFE has fibrillation properties. If the unsintered molded product obtained by paste extrusion has no substantial strength or elongation, for example, if it breaks when pulled with an elongation of 0%, it can be considered to have no fibrillation properties.

[0021] The high molecular weight PTFE preferably has a standard specific gravity (SSG) of 2.130 to 2.280. The lower limit of the standard specific gravity is more preferably 2.135, and even more preferably 2.140. The upper limit of the standard specific gravity is more preferably 2.275, and even more preferably 2.270. The standard specific gravity is measured by a water displacement method in accordance with ASTM D-792 using a sample molded in accordance with ASTM D4895-89. Since the standard specific gravity of a resin corresponds to the molecular weight, one within the above range can be said to be a high molecular weight PTFE.

[0022] Such high molecular weight PTFE is known and can be obtained by known methods. Alternatively, commercially available products can be used.

[0023] (Copolymer (A-2)) The coating composition of the present disclosure preferably further contains one or more copolymers (A-2) consisting of tetrafluoroethylene and hexafluoropropylene and / or perfluoroalkyl vinyl ether as part of the fluororesin (A), which provides a favorable effect in terms of forming a coating film with fewer defects such as pinholes.

[0024] In this disclosure, a "perfluoro(alkyl vinyl ether)" (PAVE) is an alkyl vinyl ether that does not contain a C-H bond. The PAVE constituting the above PAVE unit is represented by the general formula (1): CF2=CFO(CF2CFY 1 O) p -(CF2CF2CF2O) q -Rf (1) (In the formula, Y 1 represents F or CF3, and Rf represents a perfluoroalkyl group having 1 to 5 carbon atoms. p represents an integer of 0 to 5, and q represents an integer of 0 to 5.) and a monomer represented by general formula (2): CFX=CXOCF2OR 1 (2) (wherein X may be the same or different and represents H, F or CF3; and R1 represents a linear or branched fluoroalkyl group having 1 to 6 carbon atoms which may contain 1 to 2 atoms of at least one type selected from the group consisting of H, Cl, Br and I, or a cyclic fluoroalkyl group having 5 or 6 carbon atoms which may contain 1 to 2 atoms of at least one type selected from the group consisting of H, Cl, Br and I).

[0025] Among them, the above-mentioned PAVE is preferably a monomer represented by general formula (1), more preferably at least one selected from the group consisting of perfluoro(methyl vinyl ether), perfluoro(ethyl vinyl ether) and perfluoro(propyl vinyl ether) (PPVE), and even more preferably PPVE.

[0026] The content of PAVE units in the TFE / PAVE copolymer is preferably 1.0 to 10% by mass, more preferably 2.0% by mass or more, even more preferably 3.5% by mass or more, more preferably 8.0% by mass or less, even more preferably 7.0% by mass or less, particularly preferably 6.5% by mass or less, and most preferably 6.0% by mass or less, based on the total monomer units. The amount of PAVE units is measured by 19F-NMR. The TFE / PAVE copolymer may be a copolymer consisting of only TFE units and PAVE units.

[0027] When the copolymer (A-2) is a TFE / PAVE copolymer, the melting point is preferably 280 to 322°C, more preferably 290°C or higher, and more preferably 320°C or lower.

[0028] When the copolymer (A-2) is a TFE / PAVE copolymer, the glass transition temperature (Tg) is preferably 70 to 110° C., more preferably 80° C. or higher, and more preferably 100° C. or lower. The glass transition temperature is a value obtained by measuring dynamic viscoelasticity.

[0029] The content of the HFP units in the TFE / HFP copolymer is preferably 5 to 30% by mass, more preferably 10% by mass or more, further preferably 15% by mass or more, and more preferably 25% by mass or less, based on the total monomer units. The amount of the HFP units can be measured by 19F-NMR.

[0030] The TFE / HFP copolymer may further contain (per)fluoro(alkyl vinyl ether) (PAVE) units. The PAVE units contained in the TFE / HFP copolymer may be the same as the PAVE units described above. The TFE / PAVE copolymer does not contain HFP units, and is therefore different from the TFE / HFP / PAVE copolymer.

[0031] When the TFE / HFP copolymer is a copolymer containing TFE units, HFP units, and PAVE units (hereinafter also referred to as "TFE / HFP / PAVE copolymer"), the mass ratio (TFE / HFP / PAVE) is preferably 70-99.8 / 0.1-25 / 0.1-25 (mass%). The mass ratio (TFE / HFP / PAVE) is more preferably 75-98 / 1.0-25 / 1.0-10 (mass%). The TFE / HFP / PAVE copolymer preferably contains HFP units and PAVE units in a total amount of 1 mass% or more based on the total monomer units.

[0032] In the above TFE / HFP / PAVE copolymer, the HFP unit is preferably 25% by mass or less of the total monomer units. The content of the HFP unit is more preferably 20% by mass or less. The content of the HFP unit is preferably 0.1% by mass or more, more preferably 1% by mass or more, and particularly preferably 2% by mass or more. The content of the HFP unit can be measured by 19F-NMR method.

[0033] The content of the PAVE unit is more preferably 20% by mass or less, further preferably 10% by mass or less, and particularly preferably 3% by mass or less. The content of the PAVE unit is preferably 0.1% by mass or more, more preferably 1% by mass or more. The content of the PAVE unit can be measured by 19F-NMR method.

[0034] The TFE / PAVE copolymer and the TFE / HFP copolymer may further contain other ethylenic monomer (α) units. The other ethylenic monomer (α) units are not particularly limited as long as they are monomer units copolymerizable with TFE, HFP, and PAVE, and examples thereof include fluorine-containing ethylenic monomers such as vinyl fluoride (VF), vinylidene fluoride (VdF), trifluoroethylene (TrFE), and chlorotrifluoroethylene (CTFE), and non-fluorinated ethylenic monomers such as ethylene, propylene, and alkyl vinyl ether. The content of the other ethylenic monomer (α) units is preferably 0 to 25% by mass, and more preferably 0.1 to 25% by mass.

[0035] When the copolymer (A-2) is a TFE / HFP / PAVE / other ethylenic monomer (α) copolymer, the mass ratio (TFE / HFP / PAVE / other ethylenic monomer (α)) is preferably 70-98 / 0.1-25 / 0.1-25 / 0.1-25 (mass%). The TFE / HFP / PAVE / other ethylenic monomer (α) copolymer preferably contains 1 mass% or more of monomer units other than TFE units in total.

[0036] The melting point of the TFE / HFP copolymer is preferably 200 to 322°C, more preferably over 200°C, even more preferably 210°C or higher, more preferably 300°C or lower, and even more preferably 280°C or lower.

[0037] The glass transition temperature (Tg) of the TFE / HFP copolymer is preferably 60 to 110° C., more preferably 65° C. or higher, and more preferably 100° C. or lower. The glass transition temperature is a value obtained by measuring dynamic viscoelasticity.

[0038] The polymer (A-2) can be produced by a conventional method such as emulsion polymerization or suspension polymerization, for example, by appropriately mixing monomers that are structural units of the polymer (A-2) and additives such as a polymerization initiator. Among these, the polymer (A-2) is preferably produced by emulsion polymerization.

[0039] The polymer (A-2) preferably has an MFR value measured at 372°C under a load of 5 kg within the range of 1 to 30 (g / 10 min). This range is preferable because it is easy to obtain the above-mentioned amount of functional groups by the terminal functional groups. The lower limit of the MFR is more preferably 3 (g / 10 min), and even more preferably 10 (g / 10 min). The upper limit of the MFR is more preferably 28 (g / 10 min), and even more preferably 25 (g / 10 min).

[0040] In the coating composition of the present disclosure, the mass ratio of the high molecular weight polytetrafluoroethylene (A-1) to the copolymer (A-2) is preferably (A-1) / (A-2)=10 / 90 to 90 / 10. The lower limit of the mass ratio is more preferably 10.5 / 89.5, and even more preferably 11 / 89. The upper limit of the mass ratio is more preferably 89.5 / 10.5, and even more preferably 89 / 11. By keeping it within such a range, it is preferable in that a coating film having few defects such as pinholes and excellent insulation and abrasion resistance can be formed.

[0041] (Polyamide-imide resin and / or epoxy resin (B)) The coating composition of the present disclosure contains a polyamideimide resin and / or an epoxy resin. This is preferable because it can form a coating film with excellent adhesion to the substrate. The polyamideimide resin and / or the epoxy resin that can be used in the present disclosure will be described in detail below.

[0042] (Polyamide-imide resin) A polyamide-imide resin is typically a resin obtained by reacting an acid component with a diisocyanate component, and has a structural portion derived from the acid component and a structural portion derived from the diisocyanate component.

[0043] (acid component) The acid component is not particularly limited, and includes at least an aromatic tribasic acid anhydride and / or an aromatic tribasic acid halide. In one embodiment, the acid component preferably includes at least an aromatic tribasic acid anhydride, and more preferably includes trimellitic anhydride. Therefore, in one embodiment, the polyamide-imide resin preferably has a structure represented by the following general formula (I).

[0044] [ka]

[0045] In the structure represented by general formula (1), R is an organic group (structural portion) derived from a diisocyanate component, and n is an integer of 1 or more.

[0046] The content of trimellitic anhydride is preferably 50 mol % or more based on the total amount of acid components constituting the polyamide-imide resin (100 mol %). In one embodiment, the content of trimellitic anhydride may be 100 mol %.

[0047] In another embodiment, the content of trimellitic anhydride may be 50 mol % to 95 mol % based on the total amount of acid components constituting the polyamideimide resin (100 mol %), and other acid components may be contained in an amount of 5 mol % to 50 mol %. As the other acid component, for example, a dicarboxylic acid can be used, such as succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, phthalic acid, isophthalic acid, or terephthalic acid. Moreover, these compounds may be used alone or in combination of two or more kinds.

[0048] (Diisocyanate component) The diisocyanate component preferably contains at least an aromatic diisocyanate. Therefore, in one embodiment, in the above general formula (I), R is preferably an organic group derived from an aromatic diisocyanate. Based on the total amount of the diisocyanate components constituting the polyamide-imide resin (100 mol%), the content of the aromatic diisocyanate is preferably 30 mol% or more, and more preferably 40 mol% or more. In one embodiment, the content of the aromatic diisocyanate may be 100 mol%.

[0049] The aromatic diisocyanate includes at least one selected from the group consisting of 4,4'-diphenylmethane diisocyanate, 3,3'-dimethyl-4,4'-diisocyanatobiphenyl, 2,4-toluene diisocyanate, and 2,6-toluene diisocyanate. Among the aromatic diisocyanates, 4,4'-diphenylmethane diisocyanate is preferred. Therefore, based on the total amount of diisocyanate components constituting the polyamideimide resin, the content of aromatic diisocyanates including 4,4'-diphenylmethane diisocyanate is preferably 30 mol% or more, more preferably 40 mol% or more, and may be 100 mol%.

[0050] In one embodiment, the content of 4,4'-diphenylmethane diisocyanate may be 100 mol% based on the total amount of diisocyanate components constituting the polyamideimide resin. In another embodiment, the content of 4,4'-diphenylmethane diisocyanate may be 30 mol% to 95 mol% and the content of other aromatic diisocyanates may be 5 mol% to 70 mol% based on the total amount of diisocyanate components constituting the polyamideimide resin.

[0051] In the coating composition of the present disclosure, the polyamideimide resin preferably has a number average molecular weight of 10,000 to 40,000. Use of one within such a range is preferred in that a coating film having excellent adhesion to the substrate can be formed.

[0052] The lower limit of the number average molecular weight is preferably 12000, and more preferably 14000 or more. The upper limit of the number average molecular weight is preferably 37000, and more preferably 33000.

[0053] In this specification, the number average molecular weight of the polyamideimide resin is a value measured by gel permeation chromatography (GPC).

[0054] (Epoxy resin) In the present disclosure, an epoxy resin is a compound having two or more oxirane rings (epoxy groups) in the molecule.

[0055] The epoxy resin is not particularly limited, and known epoxy resins can be used.Specific examples include bisphenol A type epoxy resin, bisphenol F type epoxy resin, brominated epoxy resin, bisphenol S type epoxy resin, diphenyl ether type epoxy resin, hydroquinone type epoxy resin, naphthalene type epoxy resin, biphenyl type epoxy resin, fluorene type epoxy resin, bisphenol A type novolac epoxy resin, phenol novolac type epoxy resin, orthocresol novolac type epoxy resin, dicyclopentadiene phenol type epoxy resin, trishydroxyphenylmethane type epoxy resin, trifunctional type epoxy resin, tetraphenylolethane type epoxy resin, tetrafunctional type epoxy resin, hydrogenated bisphenol A type epoxy resin, bisphenol A nucleus-containing polyol type epoxy resin, polypropylene glycol type epoxy resin, glycidyl ester type epoxy resin, glycidylamine type epoxy resin, glyoxal type epoxy resin, alicyclic type epoxy resin, alicyclic polyfunctional epoxy compound, heterocyclic type epoxy resin such as triglycidyl isocyanate (TGIC).

[0056] The epoxy resin preferably has a number average molecular weight of 200 to 2000. The lower limit of the number average molecular weight is preferably 250, and more preferably 300 or more. The upper limit of the number average molecular weight is preferably 2400, and more preferably 2200.

[0057] In this specification, the number average molecular weight of the epoxy resin is a value measured by gel permeation chromatography (GPC).

[0058] (Mixing ratio) In the coating composition of the present disclosure, the mass ratio of the fluororesin (A) to the polyamideimide resin is preferably fluororesin (A) / polyamideimide resin=40 / 60 to 70 / 30. The lower limit of the mass ratio is more preferably 41 / 59 and even more preferably 42 / 58. The upper limit of the mass ratio is more preferably 69 / 31 and even more preferably 68 / 32. By keeping it within such a range, it is preferable in that a coating film excellent in insulation, abrasion resistance, and adhesion to the substrate can be formed.

[0059] In the coating composition of the present disclosure, the mass ratio of the fluororesin (A) to the epoxy resin is preferably fluororesin (A) / epoxy resin = 30 / 70 to 70 / 30. The lower limit of the mass ratio is more preferably 31 / 69, and even more preferably 32 / 68. The upper limit of the mass ratio is more preferably 69 / 31, and even more preferably 68 / 32. By keeping it within such a range, it is preferable in that a coating film excellent in insulation, abrasion resistance, and adhesion to the substrate can be formed.

[0060] When the coating composition of the present invention contains both a polyamideimide resin and an epoxy resin, the mass ratio of the fluororesin (A) to the polyamideimide resin and epoxy resin (B) is preferably fluororesin (A) / (B) = 40 / 60 to 70 / 30.

[0061] (Organic solvent (C)) The coating composition of the present disclosure contains an organic solvent (C). In the present disclosure, the fluororesin (A), polyamideimide resin and / or epoxy resin (B) are preferably dissolved and / or dispersed in an organic solvent. More specifically, the coating composition is preferably in a state in which the polyamideimide resin and / or epoxy resin (B) is dissolved in the organic solvent (C) and the fluororesin (A) that is difficult to dissolve in the solvent is dispersed therein.

[0062] Forming a coating film from such a composition is preferable in that a uniform coating film can be formed and the properties of the fluororesin, such as low friction, can be fully exhibited.

[0063] The organic solvent (C) that can be used in the present disclosure is preferably one that can dissolve polyamide-imide resins and epoxy resins and can easily disperse fluororesins, such as N-methylpyrrolidone, N-ethyl-2-pyrrolidone (NEP), 3-methoxy-N,N-dimethylpropanamide, N-butyl-2-pyrrolidone (NBP), methyl ethyl ketone, methyl isobutyl ketone, and diisobutyl ketone.

[0064] The organic solvent (C) may be a mixed solvent of two or more of the organic solvents described above, or may contain other organic solvents or water within a range that does not impede the above-mentioned object. In the organic solvent (C), the above-mentioned components (A) and (B) are present in a dispersed or dissolved state.

[0065] The coating composition of the present disclosure preferably contains the organic solvent (C) in a proportion of 50 to 90 (mass %) relative to the total amount of the composition. The lower limit is more preferably 55 mass %, and even more preferably 60 mass %. The upper limit is more preferably 85 mass %, and even more preferably 80 mass %.

[0066] (Other Ingredients) The coating composition of the present disclosure may be a composition consisting of only the fluororesin (A), the polyamideimide resin and / or the epoxy resin (B), and the organic solvent (C), or may further contain other components as necessary.

[0067] Other ingredients that may be included include water, fillers, colorants, and the like.

[0068] (viscosity) The coating composition of the present disclosure preferably has a viscosity of 100 to 40,000 cps. By setting the viscosity within the above range, workability in the coating process can be improved. Furthermore, it is also preferable in terms of obtaining a predetermined film thickness.

[0069] The above viscosity is a value measured at 25°C using a B-type viscometer as specified in JIS Z8803. The lower limit of the paint used for spray coating or the like is more preferably 110 cps, and even more preferably 120 cps. The upper limit is preferably 3,000 cps, and even more preferably 2,500 cps. The lower limit of the paint used for dispensers or roll coaters is more preferably 4,000 cps, and even more preferably 5,000 cps. The upper limit is more preferably 38,000 cps, and even more preferably 35,000 cps.

[0070] The viscosity can be adjusted to fall within the above-mentioned range by appropriately adjusting the composition of the coating composition, the amount of solvent, and the molecular weight of the component of the resin that dissolves in the solvent.

[0071] (Paint manufacturing method) The coating composition of the present disclosure can be produced by mixing the above-mentioned components. Appropriate crushing can be performed by using various known mills such as a bead mill, a ball mill, a three-roll mill, etc., combining these as necessary, adjusting the crushing conditions, adjusting the crushing time, adjusting the blending of the resin components used in combination, etc.

[0072] (Paint film) The coating film formed by the coating composition of the present disclosure is also within the scope of the present disclosure. The coating film can be formed by a general method.

[0073] The coating film of the present disclosure preferably has a friction coefficient of 0.4 or less, measured by the method described in the Examples of this specification. By having such abrasion resistance, the coating film can be made to have excellent strength and durability, and can be made to be applicable to applications requiring sliding properties. The friction coefficient means a value measured by the method described in the Examples. The friction coefficient is more preferably less than 0.3, and even more preferably less than 0.2.

[0074] The coating film of the present disclosure preferably has an abrasion resistance index of 500 or more as measured by the method described in the Examples of this specification. The coating film of the present disclosure can be a coating film that can maintain sliding properties for a long period of time, and can be a coating film that can be applied to applications where sliding properties are required. The sliding durability means a value measured by the method described in the Examples. The abrasion resistance index is more preferably 600 or more, and even more preferably 700 or more.

[0075] The coating film of the present disclosure preferably has a thickness of 5 to 120 μm as measured by the method described in the Examples of this specification. The lower limit of the thickness is more preferably 10 μm, and even more preferably 15 μm. The upper limit of the thickness is more preferably 110 μm, and even more preferably 105 μm. By keeping the thickness within this range, it is preferable in that a coating film having few defects such as pinholes and coating film bubbles and excellent insulation properties and abrasion resistance can be formed.

[0076] (Applications of coating compositions) The applications to which the coating composition of the present disclosure can be applied are not particularly limited, and include, in addition to painting bearings for electric vehicles, industrial products such as office automation (OA) rolls, OA belts, OA separation claws, papermaking rolls, and film manufacturing calendar rolls; injection molds, molds for polystyrene foam molding, and other mold releases; mold release plates for plywood and decorative panel manufacturing; industrial containers (especially for the semiconductor industry); tools such as saws and files; household products such as irons, scissors, and knives; metal foils; electric wires; sliding bearings for food processing machines, packaging machines, and textile machines; sliding parts for cameras and watches; automobile parts such as pipes, valves, and bearings; snow shovels; plows; chutes, etc. The coating composition of the present disclosure can be particularly suitably used for painting bearings for electric vehicles.

[0077] The present disclosure also relates to a coating film obtained using the above-mentioned coating composition, and an article and a bearing having the coating. Furthermore, the present disclosure also relates to an article having the above-mentioned bearing. Examples of such articles include transportation equipment such as automobiles, industrial equipment such as machine tools and semiconductor manufacturing equipment, and power generation equipment such as wind power generators. In particular, the present disclosure can be suitably used in equipment in which a large current flows through the bearing. EXAMPLES

[0078] The present disclosure will be specifically described below based on examples. In the tables, "%" and "parts" respectively indicate "% by mass" and "parts by mass".

[0079] [Examples 1 to 9 and Comparative Examples 1 to 7] The components shown in Table 1 were mixed in the prescribed amounts, and various resin raw materials were dispersed in a mixed solvent of N-methylpyrrolidone and methyl isobutyl ketone (mixing ratio: 7 / 3) using a stirring mill to obtain a coating composition. The proportion of the mixed solvent in the total amount of the coating composition was 75% (mass ratio). The properties of the film formed from this coating composition are shown in Table 1. The components in the table are as follows:

[0080] High molecular weight PTFE: Non-melt processable and non-fibrillating PTFE. Standard specific gravity: 2.170. Low molecular weight PTFE: PTFE that is non-melt processable and does not have fibrillating properties. It is not possible to mold samples for measuring the standard specific gravity. TFE / HFP copolymer: TFE / HFP=78 / 22 (mass%). Melting point: 218° C. MFR: 17 (g / 10 min). TFE / PPVE copolymer: TFE / PPVE=96 / 4 (mass%). Melting point: 314°C. MFR: 24 (g / 10 min). TFE / HFP / PPVE copolymer: TFE / HFP / PPVE=79 / 19 / 2 (mass%). Melting point: 256°C. MFR: 21 (g / 10 min). Polyamide-imide resin Molecular weight 15,000: Trimellitic anhydride·4,4'-diphenylmethane diisocyanate polycondensate. Polyamide-imide resin Molecular weight 25,000: Trimellitic anhydride·4,4'-diphenylmethane diisocyanate polycondensate. Polyamide-imide resin Molecular weight 30,000: Trimellitic anhydride·4,4'-diphenylmethane diisocyanate polycondensate. Epoxy resin molecular weight 340: Bisphenol A type epoxy resin. Epoxy resin molecular weight 800: Bisphenol A type epoxy resin. Epoxy resin molecular weight 2000: Bisphenol A type epoxy resin.

[0081] (Molecular weight of polyamide-imide resin) The values ​​were measured by gel permeation chromatography (GPC). The apparatus used was a GEL PERMEATION CHROMATOGRAPH HLC-8020 manufactured by Tosoh Corporation, the column was a Shodex GPC KD-806M manufactured by Showa Denko K.K., and the solvent was dimethylformamide (DMF) tetrahydrofuran.

[0082] (Molecular weight of epoxy resin) The values ​​were measured by gel permeation chromatography (GPC), using a GEL PERMEATION CHROMATOGRAPH HLC-8020 manufactured by Tosoh Corporation, a Shodex GPC KF-803L column manufactured by Showa Denko K.K., and tetrahydrofuran (THF) as the solvent.

[0083] (Painting method) The above paint was applied to a SUS304 substrate that had been degreased and blasted. In Tables 1 and 2, the coating was formed by drying at 100° C. for 30 minutes and then heating at 280° C. for 30 minutes. In Tables 3 and 4, the coating was formed by drying at 100° C. for 30 minutes and then heating at 180° C. for 30 minutes.

[0084] The resulting coating film was evaluated according to the following methods. (Film thickness) The thickness of the coating was measured using an eddy current type coating thickness meter (Kett Electric Laboratory).

[0085] (Breakdown voltage (kV)) Using a dielectric breakdown tester YST-243-100RHO (manufactured by Yamayo Test Instruments Co., Ltd.), the dielectric breakdown voltage of the coating film was measured in accordance with JIS C2110-1 under the conditions of AC voltage step-up method (short-time method, 50 Hz), measurement temperature: 23°C, surrounding medium: insulating oil, and test electrodes: Φ20 sphere / Φ25 cylinder.

[0086] (friction coefficient) The friction coefficient of the coating was measured using a friction and wear tester Tribogear 38 (manufactured by Shinto Scientific Co., Ltd.) under the conditions of Baudenleben type, steel ball 8 mmΦ, linear velocity: 0.27 cm / sec, and load: 1 kgf.

[0087] (Adhesion to substrate SAICAS (kN / m)) The adhesive strength with the substrate was measured using a surface and interface property analyzer SAICAS (manufactured by Daipla Wintes).

[0088] (Wear resistance index) A friction and wear tester, Friction Player FPR2200 (manufactured by Rhesca), was used to measure the time until the coating film was worn down by 10 μm by reciprocating sliding with a counter material: Φ5 mm zirconia ball, load: 2 kgf, linear speed: 20 mm / sec, and travel distance: 10 mm. In Tables 1 and 2, the wear resistance index was obtained as an index when Comparative Example 2 was set to 100, and in Tables 3 and 4, the index when Comparative Example 5 was set to 100.

[0089] [Table 1]

[0090] [Table 2]

[0091] [Table 3]

[0092] [Table 4] In the above tables, the amounts blended are in mass %.

[0093] It is clear from the results in Tables 1 to 5 above that the coating composition of the present disclosure has excellent insulating properties and abrasion resistance, and is particularly suitable for coating bearings for electric vehicles. [Industrial Applicability]

[0094] The coating composition of the present disclosure can be suitably used for coating bearings for electric vehicles, etc.

Claims

1. A coating composition comprising a fluororesin (A) containing, in whole or in part, high molecular weight polytetrafluoroethylene (A-1), a polyamideimide resin and / or an epoxy resin (B), and an organic solvent (C).

2. The coating composition according to claim 1, wherein the fluororesin (A) further contains one or more copolymers (A-2) consisting of tetrafluoroethylene and hexafluoropropylene and / or perfluoroalkyl vinyl ether.

3. The coating composition according to claim 2, wherein the copolymer (A-2) has a melt flow rate of 1 to 30 (g / 10 min).

4. The coating composition according to claim 2 or 3, wherein the mass ratio of the high molecular weight polytetrafluoroethylene (A-1) to the copolymer (A-2) is (A-1) / (A-2)=10 / 90 to 90 / 10.

5. 3. The coating composition according to claim 1, wherein the mass ratio of the fluororesin (A) to the polyamideimide resin is fluororesin (A) / polyamideimide resin=40 / 60 to 70 / 30.

6. 3. The coating composition according to claim 1, wherein the polyamide-imide resin has a number average molecular weight of 10,000 to 40,000.

7. 3. The coating composition according to claim 1 or 2, wherein the mass ratio of the fluororesin (A) to the epoxy resin is fluororesin (A) / epoxy resin=30 / 70 to 70 / 30.

8. 3. The coating composition according to claim 1, wherein the epoxy resin has a number average molecular weight of 200 to 2,500.

9. The coating composition according to claim 1, wherein the polyamideimide resin and / or epoxy resin (B) is a polyamideimide resin, the fluororesin (A) further comprises one or more copolymers (A-2) consisting of tetrafluoroethylene and hexafluoropropylene and / or perfluoroalkyl vinyl ether, the copolymer (A-2) having a melt flow rate of 1 to 30 (g / 10 min), the mass ratio of the high molecular weight polytetrafluoroethylene (A-1) to the copolymer (A-2) is (A-1) / (A-2)=5 / 95 to 55 / 45, the mass ratio of the fluororesin (A) to the polyamideimide resin is fluororesin (A) / polyamideimide resin=40 / 60 to 70 / 30, and the polyamideimide resin has a number average molecular weight of 10,000 to 40,000.

10. The coating composition according to claim 1, wherein the polyamideimide resin and / or the epoxy resin (B) is an epoxy resin, the fluororesin (A) further comprises one or more copolymers (A-2) consisting of tetrafluoroethylene and hexafluoropropylene and / or perfluoroalkyl vinyl ether, the copolymer (A-2) having a melt flow rate of 1 to 30 (g / 10 min), the mass ratio of the high molecular weight polytetrafluoroethylene (A-1) to the copolymer (A-2) being (A-1) / (A-2)=5 / 95 to 55 / 45, the mass ratio of the fluororesin (A) to the epoxy resin being fluororesin (A) / epoxy resin being 30 / 70 to 70 / 30, and the number average molecular weight of the epoxy resin being 200 to 2000.

11. A coating formed from the coating composition according to claim 1 or 2.

12. An article having the coating of claim 11.

13. A bearing having the coating of claim 11.

14. An article comprising the bearing of claim 13.

Citation Information

Patent Citations

  • Tetrafluoroethylene copolymer composition for coating

    JP1999513052A

  • Coat for slide members and slide member having the same

    JP2018188621A

  • Coating composition and coated article

    JP2020176216A

  • Water-soluble fluororesin coating composition

    JP2021091754A

  • Roller bearing

    JP2022042162A